Computational flow modeling for chemical reactor engineering - Ranade, Vivek V. (San Diego : Academic Press, 2002)
This book describes how modeling fluid flow in chemical reactors may offer solutions that improve design, operation, and performance of reactors. Chemical reactors are any vessels, tubes, pipes, or tanks in which chemical reactions take place. Computational Flow Modeling for Chemical Reactor Engineering will show the reactor engineer how to define the specific roles of computational flow modeling, select appropriate tools, and apply these tools to link reactor hardware to reactor performance. Overall methodology is illustrated with numerous case studies. Industry has invested substantial funds in computational flow modeling which will pay off only if it can be used to realize significant performance enhancement in chemical reactors. No other single source exists which provides the information contained in this book.
Reactor engineering and flow modeling -- Mathematical modeling of flow processes -- Turbulent flow processes -- Multiphase flow processes -- Reactive flow processes -- Numerical solution of model equations -- Numerical solution of complex flow models -- Computational tools for simulating flow processes -- Flow modeling for reactor engineering -- Stirred reactors -- Bubble column reactors -- Fluidized bed reactors -- Fixed bed and other types of reactors.
Includes bibliographical references and indexes.
Keywords: Chemical reactors -- Fluid dynamics -- Mathematical models; Electronic books